Reducing Provider Workload While Preserving Patient Safety: A Randomized Control Trial Using 2-Way Texting for Postoperative Follow-up in Zimbabwe's Voluntary Medical Male Circumcision Program. (1st January 2020) - Feldacker, Caryl; Murenje, Vernon; Holeman, Isaac; Xaba, Sinokuthemba; Makunike-Chikwinya, Batsirai; Korir, Michael; Gundidza, Patricia T.; Holec, Marrianne; Barnhart, Scott; Tshimanga, Mufuta
Abstract : Background: Voluntary medical male circumcisions (MCs) are safe: the majority of men heal without complication. However, guidelines require multiple follow-up visits. In Zimbabwe, where there is high mobile phone ownership, severe health care worker shortages, and rapid MC scale up intersect, we tested a 2-way texting (2wT) intervention to reduce provider workload while safeguarding patient safety. Setting: Two high-volume facilities providing MC near Harare, Zimbabwe. Methods: A prospective, unblinded, noninferiority, randomized control trial of 722 adult MC clients with cell phones randomized 1:1. 2wT clients (n = 362) responded to a daily text with in-person follow-up only if desired or an adverse event (AE) was suspected. The control group (n = 359) received routine in-person visits. All men were asked to return on postoperative day 14 for review. AEs at ⩽day 14 visit and the number of in-person visits were compared between the groups. Results: Cumulative AEs were identified in 0.84% [95% confidence interval (CI): 0.28 to 2.43] among routine care men as compared with 1.88% (95% CI: 0.86 to 4.03) of 2wT participants. Noninferiority cannot be ruled out (95% CI: −∞ to +2.72); however, AE rates did not differ between the groups ( P = 0.32). 2wT men attended an average of 0.30 visits as compared with 1.69 visits among routine care men, a significant reduction ( P < 0.001). Conclusions: Although noninferiority cannot be demonstrated, increased AEs in the 2wT arm likely reflect improved AE ascertainment. 2wT serves as a proxy for active surveillance, improving the quality of MC patient care. 2wT also reduced provider workload. 2wT provides an option for men to heal safely at home, returning to care when desired or if complications arise. 2wT should be further tested to enable widespread scale-up. Abstract : Supplemental Digital Content is Available in the Text.